PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA PERAWAT MELALUI TURNOVER INTENTION PERAWAT PADA RUMAH SAKIT SYAFIRA PEKANBARU - Jefri Anderson; Kurniawaty Fitri; Marhadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study was conducted at Hospital Syafira Pekanbaru located on Jalan Sudirman, Pekanbaru. The purpose of this study was to determine the effect of leadership, non-physical work environment on turnover intention through job satisfaction. The study population was 87 and the model used is a model census. Research variables used are leadership and non-physical work environment as an independent variable, turnover intention and job satisfaction as the dependent variable. This research method using path analysis supported by SPSS 21 for windows. The results of this study show that leadership influence positively and significantly to job satisfaction, work environment non-physical positive and significant impact on job satisfaction, leadership a significant negative effect on turnover intention, workplace non-physical negative and significant effect on turnover intention, job satisfaction effect negative and significant impact on turnover intention and also the leadership of no effect through job satisfaction on turnover intention. Because each individual proven leadership variable, non-physical work environment and satisfaction significantly influence turnover intention, it is recommended that the hospital management more attention to the level of leadership and job satisfaction of nurses.Keyword: Leadership, Traning, Non-physical Work Environment, Job , Turnover Intention, Job Satisfacition